Penurunan Indeks Glikemik Nasi Putih dengan Penambahan Ekstrak Serai dan Daun Salam - Fairuz Fajriah; Didah Nur Faridah; Dian Herawati (Jurnal Teknologi dan Industri Pangan, 2022)
Diabetes mellitus (DM) is one of the non-communicable diseases that could be prevented by consumption of foods capable of maintaining blood glucose at a safe level. Phenolic compounds are components in food that affect blood glucose levels. Lemongrass and bay leaf are Indonesian spices commonly used for cooking and contain phenolic compounds that have potential as antidiabetic compounds. The aim of this study was to evaluate the effect of adding lemongrass and bay leaves water extracts on the GI value of cooked white rice. Lemongrass and bay leaves containing phenolic compounds were extracted with water and added to white rice during the cooking process or sprayed on cooked rice. The glycemic index of the tested food measured using the ISO 26642 method showed that the addition of lemongrass extract and a combination of lemongrass and bay leaf extract with total phenolic content (TPC) of 570 mg GAE/100 g and 565 mg GAE/100 g, respectively, on cooked white rice IR 64 resulted in the GI reduction in the cooked rice by 23 and 27%, respectively. These reduction was higher than those resulted from the addition of lemon grass or the combination of lemon grass and bay leaf extract during the cooking process, i.e. 9 and 13%, respectively.